Auger Ionization Beats Photo‐Oxidation of Semiconductor Quantum Dots: Extended Stability of Single‐Molecule Photoluminescence1. Issue 13 (27th February 2015) - Yamashita, Shin‐ichi; Hamada, Morihiko; Nakanishi, Shunsuke; Saito, Hironobu; Nosaka, Yoshio; Wakida, Shin‐ichi; Biju, Vasudevanpillai
Abstract Despite the bright and tuneable photoluminescence (PL) of semiconductor quantum dots (QDs), the PL instability induced by Auger recombination and oxidation poses a major challenge in single‐molecule applications of QDs. The incomplete information about Auger recombination and oxidation is an obstacle in the resolution of this challenge. Here, we report for the first time that Auger‐ionized QDs beat self‐sensitized oxidation and the non‐digitized PL intensity loss. Although high‐intensity photoactivation insistently induces PL blinking, the transient escape of QDs into the ultrafast Auger recombination cycle prevents generation of singlet oxygen (1O2) and preserves the PL intensity. By the detection of the NIR phosphorescence of 1O2 and evaluation of the photostability of single QDs in aerobic, anaerobic, and 1O2 scavenger‐enriched environments, we disclose relations of Auger ionization and 1O2‐mediated oxidation to the PL stability of single QDs, which will be useful during the formulation of QD‐based single‐molecule imaging tools and single‐photon devices.